Perancangan PSS dan POD-LQR Menggunakan PSO pada Sistem Tenaga Listrik Bermesin Tunggal dengan TCSC - Hatta Imaduddien Wiennetou; Sarjiya (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Nowadays sudden change in load could lead to instability in power system. Power system needs to be protected to prevent loss synchronization. Power system stability could be increased by installing power system stabilizer (PSS) and thyristor controlled series capacitor (TCSC). A TCSC increases power system stability with helps from power oscillation damping (POD). The performances of PSS and POD are depended on its controller structure. In this research, lead-lag two stages was proposed as controller structure of PSS, and proposed controller structure for POD is linear quadratic regulator (LQR). The controller parameters of PSS and POD were designed by using particle swarm optimization (PSO). The dynamic and stability of power system with proposed controllers was investigated in single machine infinite bus (SMIB) with 0.2 pu increment in electrical power as disturbance. The main objective of this study is to investigate the effectiveness of damping function of proposed method in three different loads. The simulation results show that proposed controller could increase power system stability and reliable in different loads.